Physical activity and nutrition guidelines to help with the fight against COVID-19. Issue 1 (2nd January 2021) - Khoramipour, Kayvan; Basereh, Aref; Hekmatikar, Amirhoseein Ahmadi; Castell, Lindy; Ruhee, Ruheea Taskin; Suzuki, Katsuhiko
ABSTRACT: As the world is witnessing the epidemic of coronavirus disease 2019, emerging genetics and clinical pieces of evidence suggest a similar immunopathology to those of severe acute respiratory syndrome and Middle East respiratory syndrome. Staying at home to prevent the spread of the virus and consequently being largely inactive is associated with unintended consequences. These can actually enhance the infection risk and exacerbate poor health conditions including impaired immune function. Physical activity is a feasible way of improving health, particularly physical and mental health in a time of social isolation. However, people with certain health conditions in these circumstances may need a special physical activity programme in addition to any exercise they may already be performing via online programmes. This review aims to provide practical guidelines during the COVID-19 quarantine period. We suggest performing aerobic, resistance training, respiratory muscle training and yoga in the healthy, and in those with upper respiratory tract illness, patients with lower respiratory tract illness should be restricted to respiratory muscle training and yoga. In addition, vitamins D and C, omega-3 fatty acids, and regular consumption of fruit and vegetables might be considered as nutritional aids to support the immune system in those affected by COVID-19.